Regulation of COL1A2, AKT3 genes, and related signaling pathway in the pathology of congenital talipes equinovarus - Wang, Ningqing; Zhang, Jiangchao; Lv, Haixiang; Liu, Zhenjiang (Frontiers in Pediatrics, 2022)
Congenital talipes equinovarus (CTEV) is one of the most common congenital limb defects in children, which is a multifactorial and complex disease that associates with many unknown genetic, social-demographic, and environmental risk factors. Emerging evidence proved that gene expression or mutation might play an important role in the occurrence and development of CTEV. However, the underlying reasons and involved mechanisms are still not clear. Herein, to probe the potential genes and related signaling pathways involved in CTEV, we first identified the differentially expressed genes (DEGs) by mRNA sequencing in pediatric patients with CTEV compared with normal children. The gene of COL1A2 was upregulated, and AKT3 was downregulated at the transcriptional level. Western blot and quantitative polymerase chain reaction (qRT-PCR) results also showed that the expression of COL1A2 in CTEV was enhanced, and the AKT3 was decreased. Furthermore, the COL1A2 Knock-in (+COL1A2) and AKT3 Knock-out (-AKT3) transgenic mice were used to verify the effects of these two genes in the CTEV, and the results of which showed that both COL1A2 and AKT3 were closely related to the CTEV. We also investigated the effect of the PI3K-AKT3 signaling pathway in CTEV by measuring the relative expression of several key genes using Western blot and qRT-PCR. In line with the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis data, the PI3K-AKT3 signaling pathway might play a potentially important role in the regulation of pathological changes of CTEV. This study will provide new ideas for the mechanism investigation and prenatal diagnosis of CTEV.